DIVERSION LEGAL RULES AS A SETTLEMENT OF CRIMINAL CASES AGAINST CHILDREN WHO COMMIT MURDER - Aulia Rahman Hakim Hasibuan; Happy Krisman Laia; Aliza Ayu Novila (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Mugging is basically a criminal act of taking someone else's property against the law followed by violence or threats of violence, even in other conditions it can also be followed by other crimes such as murder and rape. This crime is currently often committed by minors, environmental factors greatly influence the occurrence of mugging, starting from motorcycle gang groups whose members are partly minors. So that violent crimes by taking other people's property on the street are often committed by children which results in the child being in conflict with the law. Diversion is a way out for resolving children who are in conflict with the law. The purpose of this study is to determine the meaning of diversion and the rules of diversion law as well. This study is included in descriptive research with a type of normative juridical research, which uses data sources from secondary data, then the analysis method is qualitative analysis. From this study, it can be concluded that diversion is an effort to divert the settlement of juvenile criminal cases from the criminal justice process to a process outside the courts. Regulations on diversion are regulated in various laws and regulations, namely, Law on the Juvenile Criminal Justice System Number 11 of 2012 Article 6 to Article 15, which explains that diversion must be attempted at every level of examination (investigation, prosecution, and examination in court), Government Regulation Number 65 of 2015 concerning Guidelines for the Implementation of Diversion and Handling of Children Under 12 (Twelve) Years of Age, this regulation regulates the procedures and implementation of diversion, as well as special handling for children under 12 years of age who commit crimes, and Supreme Court Regulation Number 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System, this Regulation provides technical guidelines for the implementation of diversion by law enforcement officers, including judges, in handling juvenile cases.